Development of Highly Sensitive Gas Sensor Using Quartz Crystal Microbalance Dipping Method for Gas Vapour Detection - Nur Firzanah Rosnan; Mohd Kamarulzaki Mustafa (Enhanced Knowledge in Sciences and Technology, 2024)
Gas sensors play a critical role in environmental monitoring and industrial safety, particularly in detecting hazardous substances such as Volatile Organic Compounds (VOCs). This research focuses on advancing gas sensor technology through the innovative application of the Quartz Crystal Microbalance (QCM) dipping method. The research employs precise thin film deposition techniques on the QCM surface to optimize the sensor’s performance. The study systematically investigates and customizes the sensor’s sensitivity and selectivity, emphasizing its capability for VOC detection. Experimental evaluations demonstrate the sensor’s rapid response and heightened sensitivity, underscoring its potential for reliable gas detection in various applications. The customizable nature of the sensor allows for tailoring its response to specific gases, addressing the critical need for efficient and targeted detection mechanisms. This research contributes to the ongoing evolution of gas sensing technologies, providing a promising avenue for enhanced detection capabilities in diverse scenarios.